Language behaviour : acquisition and evolutionary history - Narasimhan, Rangaswamy (Language and development (New Delhi, India), 1998)
"Arguing the thesis that first language acquisition by children is not a grammatical issue in the linguistic sense but a behavioral issue in the psychological sense, Language Behavior breaks new ground in the study of first language acquisition and also in charting the evolutionary history of language behavior. Author R. Narasimhan traces the process by which children acquire their first language by living and growing up in a particular community and without any special tuition or effort. In doing so he explores several basic issues including the role played by the language community in the acquisition process; the specific stages in childrenÆs acquisition of language behavior; and the specific cognitive competencies that are prerequisites for language behavior acquisition. The author then presents a specific behavioral model̮distinct from the currently prevailing linguistics motivated models̮as a framework for understanding these issues in a unified manner. The second part of the book is devoted to charting the evolutionary history of language behavior̮what the early stages might have been and how language behavior, as we know it now, might have evolved. The last part discusses some of the more important unresolved issues in language behavior modeling. Language Behavior will be of interest to students and scholars in linguistics, cognitive psychology, psycholinguistics, ethnology, and language evolution." --Publisher description.